Geochemistry of speleothems affected by aragonite to calcite recrystallization – Potential inheritance from the precursor mineral. (1st March 2017) - Domínguez-Villar, David; Krklec, Kristina; Pelicon, Primož; Fairchild, Ian J.; Cheng, Hai; Edwards, Lawrence R.
Abstract: Formerly aragonite speleothems recrystallized to calcite result from solutions subsaturated in aragonite and supersaturated in calcite that infiltrate into the speleothem through the interconnected porosity. In most cases, the crystal replacement takes place through a thin solution film. This diagenetic process can occur under open or semi-closed geochemical conditions. Thus, secondary calcite crystals record the composition of the fluid at the time of diagenesis affected by calcite partition coefficients and fractionation factors (open system) or partly inherit the composition of the primary aragonite (semi-closed system). So, whether or not recrystallized aragonite speleothems can record reliable geochemical signals from the time of speleothem primary deposition still is an open debate. We studied a stalagmite from Eagle Cave (Spain) predominantly composed of secondary calcite that replaced aragonite, although a core of primary aragonite extending 45 mm along the growth direction was preserved at the base of the sample. We obtained Mg and Sr compositional maps, paired U–Th dating and δ 18 O and δ 13 C profiles across the diagenetic front. Additionally, two parallel isotope records were obtained along the speleothem growth direction in the aragonite and calcite sectors. Our results support that recrystallization of this speleothem took place in open system conditions for δ 18 O, δ 13 C, Mg and Sr, but in semi-closed system conditions for U and Th. The recrystallization of this sample took place during one or several events, likely after the Younger Dryas as a result of climate change influencing drip water composition. Based on compositional zoned patterns, we suggest that the advance of diagenetic fronts in this speleothem had an average rate of 50 ± 45 μm/yr. Such recrystallization rate can transform any aragonite speleothem into calcite within a few centuries. We suggest that the volume of water interacting with the speleothem at the time of recrystallization is of critical importance for inheritance of different elements. The volume of solution is controlled by (1) the discharge of water passing through the sample and (2) the lapse time between aragonite dissolution and calcite precipitation. Hydrology and hydrochemistry of the interacting solution, together with the mineralogy and texture of the speleothem are the essential controls for the diagenesis of the speleothem. Recrystallization of aragonite speleothems does not follow stratigraphical levels of the sample but occurs along sites with preferential flow paths in any sector of the speleothem. In these cases the relationship between age and distance from base is not preserved. However, alternation of periods of recrystallization with periods of aragonite precipitation causing speleothem accretion can result in recrystallized speleothems with coherent distance from the base-age relationship. Thus, early diagenesis of speleothems affected by seasonal or inter-annual oscillation of drip waters supersaturated and subsaturated in aragonite may provide best-scenario conditions for dating and preservation of paleoenvironmental records along recrystallized speleothems. However, even in this scenario, the variable discharge and the diagenetic rate control the geochemical inheritance from the primary aragonite crystals.